Giving Birth in Eighteenth-Century England - Fox, Sarah (New Historical Perspectives, 2022)
This fascinating new book radically rewrites all that we know about eighteenth-century childbirth by placing women's voices at the centre of the story. From quickening through to confinement, giving caudle, delivery andlying-in, birth was once a complex ritual that involved entire communities. Drawing on an extensive and under-researched body of materials, such as letters, diaries and recipe books, this book offers critical new perspectives on the history of the family and community. It explores the rituals of childbirth, from birthing clothing to the foods traditionally eaten before and after birth, and also how a woman's relationship with her family, husband, friends and neighbours changed during pregnancy and beyond. In this important and deeply moving study, we are invited on a detailed and emotive journey through motherhood in an age of immense intellectual and sociocultural change.